1996
DOI: 10.1677/joe.0.1510507
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity and pancreatic islet blood flow in the rat: a preferential increase in islet blood perfusion persists after withdrawal of the diet and normalization of body weight

Abstract: The aim of the present study was to evaluate the effects of diet-induced obesity on pancreatic islet blood perfusion in normal Wistar rats. Furthermore, we investigated to what extent any obesity-associated changes in islet blood flow could be reversed after reversion to a normal diet with normalization of body weight. Young adult female Wistar rats were offered a palatable mixed high-caloric diet (cafeteria diet) in addition to standard pelleted chow. Age-matched control rats received standard pelleted chow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
9
23
0
Order By: Relevance
“…Thus, the islet blood flow in partially pancreatectomized Wistar rats increased to such a magnitude that the total blood perfusion to islets in these rats reached the same level as the islet blood flow in the whole pancreas in the sham-operated animals. This finding confirms previous observations linking augmented islet blood flow to settings with increased need for insulin secretion (see Jansson & Sandler 1989, Styrud et al 1992, Atef et al 1992, 1994, Svensson et al 1996. Obviously, increased islet blood flow could constitute one mechanism for maintaining normal glucose homeostasis in the face of increased functional demand, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the islet blood flow in partially pancreatectomized Wistar rats increased to such a magnitude that the total blood perfusion to islets in these rats reached the same level as the islet blood flow in the whole pancreas in the sham-operated animals. This finding confirms previous observations linking augmented islet blood flow to settings with increased need for insulin secretion (see Jansson & Sandler 1989, Styrud et al 1992, Atef et al 1992, 1994, Svensson et al 1996. Obviously, increased islet blood flow could constitute one mechanism for maintaining normal glucose homeostasis in the face of increased functional demand, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…We have previously noted a decrease in islet blood flow 1 week after intra-abdominal sham operations in Sprague-Dawley rats (Jansson & Andersson 1997), which may reflect responses to changes in abdominal pressure or inflammatory reactions following laparotomy. GK and hybrid rats may be more sensitive to such events, in line with our previous observations that vagotomy and treatment with atropine decreases islet blood flow in hybrid rats to levels similar to those of normal Wistar rats (Svensson et al 1996).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…increased peripheral insulin resistance (Atef et al 1994). Islet blood flow is also increased in animal models of type 2 diabetes, such as GK rats (Svensson et al 1994a(Svensson et al , 1996, obese Zucker rats (Atef et al 1992) and obese-hyperglycemic mice (Carlsson et al 1996). We, and others, have previously suggested that changes in islet blood flow may influence hormone release from the islets (Jansson 1994, Moldovan et al 1996, and provide partial compensation for insufficient insulin release.…”
Section: Discussionmentioning
confidence: 99%